2022
DOI: 10.1186/s13550-022-00885-z
|View full text |Cite
|
Sign up to set email alerts
|

Is there a diagnostic benefit of late-phase abdomino-pelvic PET/CT after urination as part of whole-body 68 Ga-PSMA-11 PET/CT for restaging patients with biochemical recurrence of prostate cancer after radical prostatectomy?

Abstract: Background To assess the diagnostic value of an additional late-phase PET/CT scan after urination as part of 68 Ga-PSMA-11 PET/CT for the restaging of patients with biochemically recurrent prostate cancer (BCR). Methods This retrospective trial included patients with BCR following radical prostatectomy, who underwent standard whole-body early-phase PET/CT performed 105 ± 45 min and an additional late-phase PET/CT performed 159 ± 13 min after inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
3
5
0
Order By: Relevance
“…Interestingly, one patient with Gleason score of 4 + 4 showed more than 10 soft tissue metastases. Similar uptake of PSMA targeted tracer in lung metastases have been reported (35,36). Although [ 18 F]AlF-PSMA-137 PET/CT imaging did not change the stage of these prostate cancer patients, it showed low blood uptake and higher tumor-to-organ ratios at delayed time (Figure 7), which could improve the imaging contrast.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, one patient with Gleason score of 4 + 4 showed more than 10 soft tissue metastases. Similar uptake of PSMA targeted tracer in lung metastases have been reported (35,36). Although [ 18 F]AlF-PSMA-137 PET/CT imaging did not change the stage of these prostate cancer patients, it showed low blood uptake and higher tumor-to-organ ratios at delayed time (Figure 7), which could improve the imaging contrast.…”
Section: Discussionsupporting
confidence: 83%
“…This was thought to facilitate the detection of intraprostatic lesions, recurrent pelvic lesions, metastatic lymph node lesions and prostate bed lesions. In contrast, 68 Ga-PSMA-11 is rapidly excreted through the urethra (34), leading to significant accumulation in the bladder, and may somewhat obscure the detection of local recurrences (35).…”
Section: Discussionmentioning
confidence: 99%
“…Comparable to other publications [ 17 , 21 , 23 , 24 ], the lesion-to-background ratio increased for local recurrences, lymph node, and bone metastases. Also, the gain in the case detection rate on late imaging of 5.7% falls into the range of 0–10% reported in other publications [ 18 , 19 , 21 , 22 , 24 ]. However, the relationship between imaging of a patient at two time points is often more complex than the comparison of positive vs. negative cases.…”
Section: Discussionsupporting
confidence: 52%
“…For example, early scans in the first 10 min after radioligand injection may help to visualize pelvic lesions with pathological PSMA expression before urinary activity interferes with image interpretation [ 15 , 16 ]. On the other hand, several studies have described an increasing PSMA ligand uptake from standard to late imaging in most PCa-related lesions [ 17 22 ]. This was often paralleled by a decreasing tracer uptake of the background tissue [ 17 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morawitz et al. ( 72 ) found that 68 Ga-PSMA-11 PET/CT scanning in the late abdominal and pelvic stage after emptying the bladder was helpful to detect missed local recurrence lesions. Uprimny et al.…”
Section: Factors Affecting the Detection Ratementioning
confidence: 99%